Impact of age on anaesthesiologists' competence: A narrative review. Issue 11 (November 2016) - Giacalone, Marilù; Zaouter, Cédrick; Mion, Stefano; Hemmerling, Thomas M.
Abstract : The international anaesthesia community is getting older, in line with trends worldwide, and as men and women age there is the risk that psychophysiological decline could have an impact on clinical practice. Impairment of technical and nontechnical skills could have a negative impact on patients' safety and outcomes. The ageing process may not necessarily go hand-in-hand with a predictable pattern of decreased competence as not all aspects of functional decline are affected at the same rate and to the same extent. The development of simulation has provided a means of detecting and perhaps reversing the decline in ability associated with age. The introduction of recertification based on an assessment of competence at simulation sessions could play a crucial role in maintaining a high standard of patient care and an appropriate level of patient safety.